2016
DOI: 10.1097/01.aoa.0000489433.86071.1d
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Base Deficit in Acidemic Term Neonates

Abstract: (Am J Obstet Gynecol. 2015;213(3):373.e1–e7) A lack of oxygen during the intrapartum period is a well-known and significant factor leading to cerebral palsy and mortality in infants. The degree of risk can be estimated after delivery by examining pH levels in the umbilical artery. An arterial pH of <7.00 along with a base deficit of 12 mmol/L or higher is believed to be particularly significant in predicting morbidity. The authors of this study have attempted to evaluate this association, hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Only 22% of all cases with encephalopathy and seizures or death had a pH <7.00 (37). Another study from the same group showed that an arterial pH <7.00 significantly predicted neonatal outcomes (38), but the addition of BD (ecf) did not improve the prediction. It is also important to know that similar cord gases may have very different outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only 22% of all cases with encephalopathy and seizures or death had a pH <7.00 (37). Another study from the same group showed that an arterial pH <7.00 significantly predicted neonatal outcomes (38), but the addition of BD (ecf) did not improve the prediction. It is also important to know that similar cord gases may have very different outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…It is also important to know that similar cord gases may have very different outcomes. The relation between cord pH values of 7.00 and 7.10 is much less clear (38).…”
Section: Discussionmentioning
confidence: 98%
“…An established dataset was used . This was an observational cohort study of non‐anomalous (confirmed at postnatal discharge) singleton deliveries, at 36 +0 or more weeks' gestation, where complete and validated cord blood gas analyses were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The sampling technique involved double clamping at least 10 cm of cord immediately after delivery and taking samples in pre‐heparinized syringes and processing them within 15 min. Collection of cord gases and exclusion of unphysiological cord pH values was as previously described . Because of the logarithmic nature of pH, AV differences in H + ion concentration were used instead of pH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation